Public perception on the environmental effect of sanitation : a case study of the Polokwane Local Municipality in the Limpopo Province - Maphosa, Edie (My University, 2017)
The purpose of the study was to explore public perception on how sanitation has effects on the environment in the Polokwane Local Municipality. Quantitative, analytical research was conducted to determine community perceptions regarding the state of sanitation in Polokwane, that is to establish the perception of the effectiveness of the waste and refuse removal programme and to determine the extent of land pollution in the Polokwane Local Municipality. Data collection was done using structured questionnaires in which community members participated in the study. The total number of respondents, who were community members sampled randomly, was N = 136. The study has highlighted the areas of potential on perceptions of the community regarding the state of sanitation in Polokwane and the relationship of the perception, sanitation practices, the effectiveness of the waste and refuse removal programme and the extent of land pollution in Polokwane and settlement type. The findings of the research study include the following:  The study reveals that the Polokwane Local Municipality does not provide adequate sanitation throughout the municipality especially in the rural settlements;  The results reveal that the Polokwane Local Municipality still has a long way in the prevention and control of land pollution and river streams;  The study further finds that there is no frequent waste removal in the municipality especially in the suburban and rural settlement;  Furthermore, results reveal that there is no adequate hygiene education provision in the Polokwane Local Municipality. In conclusion, it is evident that the Polokwane Local Municipality experiences challenges of the provision of sanitation to the communities especially those who live in rural settlements. In the 21st century and two decades after democracy in South Africa, the residents of Polokwane still experiences sanitation challenges that were promised to be addressed in the dawn of democracy in 1994. Those challenges are land pollution, infrequent waste removal, illegal waste dumping, air and land pollution, river and stream pollution, inadequate hygiene education, inadequate sanitation provision in the rural settlement, lack of waste sorting options. The study recommends that the Polokwane local Municipality should provide adequate sanitation services in rural settlement. It should further develop measures to prevent environmental pollution and to foster communities to have a litter-free environment. The study further recommends that the municipality should have a frequent waste removal programme throughout the municipality even in the rural settlement and suburban areas. The municipality should prioritise community awareness campaigns to educate community members about the negative impact of littering. It is further recommended that, in addition to public awareness against littering, rubbish bins should be made available at all public places and street corners.
Thesis (MPA.) -- University of Limpopo, 2017
Keywords: Sanitation; Waste and refuse removal; Land pollution; Environmental protection; Sanitation -- South Africa -- Limpopo; Sanitation, Rural -- South Africa -- Limpopo; Urban sanitation; Refuse and refuse disposal -- South Africa -- Limpopo